Clinical Presentation of Dry Socket at Teaching Hospital of Hyderabad City (Medical Forum Monthly, 2024)
Objective: To find out frequency and clinical presentation of dry socket in Department of Oral and Maxillofacial Surgery Liaquat University of Medical & Health Sciences, Jamshoro.Study Design: Obseervational study.Place and Duration of Study: This study was carried out at Department of Oral & Maxillofacial Surgery, Liaquat University of Medical & Health Sciences, Jamshoro from Jan 2011 to June 2012.Materials and Methods: Age from 11 to 70 years with both gender groups was included in the study. They were observed for the presence of dry socket. Patients with previous history of two or more days of extraction, pain, sensitivity on gentle probing of the extraction socket and empty/ partially empty socket were included in the study. Data was analyzed using SPSS version-13.Results: Total 2300 extractions were included in study; dry socket was recorded in 66 (3.3%) routine dental extraction except 3rd molars and 598 (26%) surgical& non-surgical extraction of 3rd molar respectively. Majority of the patients belong to 3rd decade of lifeConclusion: In oral Surgery practice dry socket is unavoidable, but oral surgeons must identify additional risk factors in patients with particular medical conditions and include this information as a part of the informed consent.